SOX combined with apatinib and camrelizumab in the treatment of resectable locally advanced gastric cancer: a case report - Hu, JiKe; Li, Xuemei; Wang, Yunpeng; Xu, Bo; He, Puyi; Wang, Zhuanfang; He, Lijuan; Chen, Hao (Frontiers in Immunology, 2024)
Gastric cancer is highly prevalent in China, yet early diagnosis and overall survival rates are low.The primary treatment strategy is comprehensive therapy centered on surgery. Studies indicate that neoadjuvant chemotherapy can enhance radical resection rates and extend survival in locally advanced gastric cancer. Combining VEGFR inhibitors with chemotherapy improves efficacy in digestive system tumors, while PD-1/PD-L1 inhibitors combined with antiangiogenesis agents or chemotherapy show synergistic effects. This report presents a case of gastric adenocarcinoma (cT3N1M0) treated with SOX, apatinib mesylate, and camrelizumab as neoadjuvant therapy, followed by D2 distal gastrectomy and postoperative adjuvant therapy with the same regimen. The patient completed all treatment cycles successfully. Post-neoadjuvant therapy, only focal residual cancer cells were found in the lamina propria (pT1a). During postoperative adjuvant therapy follow-up, gastroscopic biopsy indicated a pathological complete response with no recurrence or metastasis. The patient primarily experienced dyspepsia, oropharyngeal pain, capillary proliferation, mild bone marrow suppression, nausea, and vomiting as side effects. Therefore, SOX combined with apatinib mesylate and camrelizumab shows promise for treating resectable locally advanced gastric cancer.